2018
DOI: 10.1155/2018/5864175
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Invasive Gastrointestinal Mycotypha Infection in a Patient with Neutropenia

Abstract: Gastrointestinal mucormycosis is a rare life-threatening infection to which neutropenic patients are especially vulnerable. Mycotypha microspora is a mucormycete that has not been described as a human pathogen. We discuss the successful eradication of gastrointestinal Mycotypha microspora in a neutropenic patient with simultaneous pulmonary Aspergillus fumigatus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…M. africana R.O. Novak & Backus and M. microspora are traditional dimorphic fungi (Schulz et al 1974) and have been most recently reported as new pathogens causing mucormycosis (Trachuk et al 2018).…”
Section: Mycotyphamentioning
confidence: 99%
“…M. africana R.O. Novak & Backus and M. microspora are traditional dimorphic fungi (Schulz et al 1974) and have been most recently reported as new pathogens causing mucormycosis (Trachuk et al 2018).…”
Section: Mycotyphamentioning
confidence: 99%
“…Sanger sequencing and IHC staining have been used in FFPE tissue, but most medical institutions only identify fungi based on morphological findings. [4][5][6][7][8][9] The identification of fungi only by morphological findings can lead to inadequate treatment for patients due to misdiagnosis, which can often result in fatal consequences. 10 Because of the different antifungal agents preferentially used at the initial infection stage depending on the fungus, it is necessary to identify the exact fungi present through testing methods in addition to the morphological findings.…”
Section: Introductionmentioning
confidence: 99%